Googling the Anthropocene: Fractal media and ecology. Issue 1 (1st December 2019) - Benjamin, Garfield
AbstractThe scars of humanity can be seen across the Earth. However, observing such ecological violence and their implications often requires finding the right perspective, moving beyond the spatial and temporal limits of individual humans. This article builds on discussion of the Anthropocene as a term and the anthropocentrism it implies to critique the relations between humanity, technology and ecology through posthuman perspectives. Focusing on Google's widely available tools, its problematic relation to the environment as a company and critical interventions by media artists Mishka Henner, Paolo Cirio and Geraldine Juárez, the article examines technologies that enable a 'posthuman' position from which to view the fractal activities of humanity: Google Maps and Earth; Street View; and the Google search engines. Fractals are offered as a mode of assessing the self-similar processes of mediation that define not only humanity's scalar expansion but also its shift into informational dimensions and the virtualization of ecology.